2014
DOI: 10.1016/j.rse.2014.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of missing data on the estimation of ecological indicators from satellite ocean-colour time-series

Abstract: a b s t r a c tOcean-colour remote sensing provides high-resolution and global-coverage of chlorophyll concentration, which can be used to estimate ecological indicators and to study inter-annual and long-term trends in the state of the marine ecosystem. To date, the record of ocean-colour observations is a rich one, including data from a number of sensors spanning more than three decades. The ESA Ocean-Colour Climate Change Initiative has advanced seamless merging of ocean-colour observations from missions du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 41 publications
(57 reference statements)
2
53
0
Order By: Relevance
“…To reduce missing data due to cloud cover, firstly, we applied a linear interpolation procedure (interpolating spatially-adjacent values) such that gaps were filled with the average value of the surrounding grid points. The averaging window had a width of five points and the surrounding points were weighted equally (Racault et al, 2014). Secondly, we produced 15-Day composites for pre-typhoon and 5-Day composites for post-typhoon conditions for the Typhoon Chataan case and 5-Day composites for pre-and post-typhoon conditions for the Typhoon Roke case, which had better data coverage.…”
Section: Integrated Hydrological-oceanographic Model: Calculation Conmentioning
confidence: 99%
“…To reduce missing data due to cloud cover, firstly, we applied a linear interpolation procedure (interpolating spatially-adjacent values) such that gaps were filled with the average value of the surrounding grid points. The averaging window had a width of five points and the surrounding points were weighted equally (Racault et al, 2014). Secondly, we produced 15-Day composites for pre-typhoon and 5-Day composites for post-typhoon conditions for the Typhoon Chataan case and 5-Day composites for pre-and post-typhoon conditions for the Typhoon Roke case, which had better data coverage.…”
Section: Integrated Hydrological-oceanographic Model: Calculation Conmentioning
confidence: 99%
“…Nevertheless, the deep Chla maximum may also result from photoacclimation to reduced light levels and nutrient availability and may not represent an increase in the organic carbon content [40,41]. A second limitation is that due to gaps in satellite data the right timing of the bloom may be missed [1,42]. Racault et al [42] have shown that if 40% of data are missing in an annual time-series, the RMSE and bias in estimates of timing of peak are ∼30 and 10 days respectively.…”
Section: Satellite Datamentioning
confidence: 99%
“…A second limitation is that due to gaps in satellite data the right timing of the bloom may be missed [1,42]. Racault et al [42] have shown that if 40% of data are missing in an annual time-series, the RMSE and bias in estimates of timing of peak are ∼30 and 10 days respectively. Data gaps due to clouds, high solar zenith angle and sea ice for example also reduce the length of the time series and the significance of the statistical tests.…”
Section: Satellite Datamentioning
confidence: 99%
“…Blending in-situ and satellite observations of TCHLa (e.g. AMT and SeaWiFS) may lead to more robust estimates of trends (Aiken et al, 2009;Gregg & Casey, 2010;Gregg & Rousseaux, 2014) and minimise the impact of periods of missing data (Beaulieu et al, 2013;Racault et al, 2014a).…”
Section: Trends In Total Chlorophyll-amentioning
confidence: 99%
“…However, long-term changes in these two ecological indicators remain non-trivial to evaluate (e.g. Antoine et al, 2005;Boyce et al, 2010;Brewin et al, 2012;Gregg and Conkright, 2002;Kostadinov et al, 2010;Mackas, 2011;McQuatters-Gollop et al, 2011;Racault et al, 2014a;Vantrepotte & Mélin, 2009;Vantrepotte & Mélin, 2011).…”
Section: Introductionmentioning
confidence: 99%